Links between Tenure Security and Food Security: Evidence from Ethiopia - Hosaena Ghebru; Stein Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2013)
The study uses five rounds of household panel data from Tigray, Ethiopia, collected in the period 1998–2010 to assess the impacts of a land registration and certification program that aimed to strengthen tenure security and how it has contributed to increased food availability and thus food security in this food-deficit region. Our first survey took place just a year before the intervention (the land certification program). Our panel data in combination with the "years of certificate ownership" variable allow us to assess the dynamic impacts on food (calorie) availability of strengthened tenure security. Anthropometric data also allow us to assess potential child nutrition impacts of the reform 8-12 years after its implementation. Results show that land certification appears to have contributed to enhanced calorie availability (calorie intake), and more so for female-headed households, either through enhanced land rental market participation or increased investment and productivity on owner-operated land. Results also show that members of households that accessed additional land through the land rental market had a significantly higher body mass index. Though results show that land rental market participation is enhancing production efficiency, high transaction costs in that market suggest there are still unrealized gains from trade. Thus, the recent restrictive regional land law that allows for only short-term rental contracts and does not allow more than 50 percent of land to be rented out may threaten future tenure security and may undermine the benefits from the existing tenure reform.
Keywords: I15; Q15; 330; Tenure security; land certification; food security; calorie availability; nutritional status; land rental market participation